EFFECT OF LIQUIDITY AND PROFITABILITY ON SHARE PRICES (STUDY ON CONSTRUCTION COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE) - Lestari, Elly Lestari; Moch Nurhidayat, Moch Nurhidayat; Imam Hidayat, Imam Hidayat; Yuni Setyawati, Yuni Setyawati; Yohana Marisna Febriani, Yohana Marisna Febriani (PENANOMICS: International Journal of Economics, 2024)
This study aims to analyze the effect of liquidity and profitability on share prices in construction sub sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. Liquidity is measured by the ratio of current assets to current liabilities, while profitability is measured by net profit. Data was collected from company financial reports and analyzed using the multiple linear regression method. The research results show that liquidity has a positive and significant influence on share prices, which shows that the higher a company's liquidity, the higher its ability to fulfill its operational obligations. Apart from that, profitability also has a positive and significant influence on share prices, indicating that the company's success in generating profits has an impact on increasing demand for shares and increasing share prices. Apart from that, together, liquidity and profitability also have a significant effect on share prices. This research contributes to the understanding of the factors that influence share prices in the context of construction companies.